Scalable, Metal- and Additive-Free, Photoinduced Borylation of Haloarenes and Quaternary Arylammonium Salts - Mfuh, Adelphe M. (J Am Chem Soc, 2016)
We report herein a simple, metal- and additive-free, photoinduced borylation of haloarenes, including electron-rich fluoroarenes, as well as arylammonium salts directly to boronic acids. This borylation method has a broad scope and functional group tolerance. We show that it can be further extended to boronic esters, and carried out on gram scale as well as under flow conditions.